1979
DOI: 10.1021/bi00590a022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of asbestos, iron oxide, silica, and carbon black on the microsomal availability of benzo[a]pyrene

Abstract: Particulate matter and polynuclear aromatic hydrocarbons are known to be cocarcinogenic. Using fluorescence spectroscopy, we determined that adsorption of benzoic] pyrene (BP) to iron oxide, silica, and asbestos (anthophyllite and Canadian chrysotile) results in a greatly enhanced rate of BP uptake into rat liver microsomes when compared to uptake from aqueous dispersions of BP microcrystals. Simple mixtures of BP microcrystals and particulates do not display enhanced microsomal uptake rates, an observation wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

1980
1980
1989
1989

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 34 publications
4
2
0
Order By: Relevance
“…Our results and those of Lakowicz et al (10)(11)(12) showed that chemical carcinogen is more readily accessible to the microsomal enzymes when it is presented as a compound adsorbed onto the particles, and we found that this phenomenon has a biological value at least in the Ames test. In view of data presented above, the amplifying effect of asbestos exposure and cigarette smoking on the incidence of lung cancer (16) is clearly understandable.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Our results and those of Lakowicz et al (10)(11)(12) showed that chemical carcinogen is more readily accessible to the microsomal enzymes when it is presented as a compound adsorbed onto the particles, and we found that this phenomenon has a biological value at least in the Ames test. In view of data presented above, the amplifying effect of asbestos exposure and cigarette smoking on the incidence of lung cancer (16) is clearly understandable.…”
Section: Resultssupporting
confidence: 85%
“…Our results are easily understandable in the light of work done by Lakowicz et al (10)(11)(12), which showed that adsorption of BaP onto asbestos or other particles increases membrane uptake of BaP. This was not related to the specific minerological character of different types of asbestos (10).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Our results are supported by studies of Lakowicz and colleagues who document by fluorimetry the increased transport of BaP to artificial membranes and microsomes when the hydrocarbon is adsorbed on a variety of particulates (16)(17)(18). Dispersions and particles of BaP do not transfer readily to membranes indicating an important, although undefined, role of the "carrier" mineral.…”
Section: Discussion Cellular Uptake and Metabolism Of Bapsupporting
confidence: 86%